The stories we tell about food: Understanding narratives of food environments and coping with loss of food access - Miller, Michael J. (Kansas State University, 2020)
This dissertation explores and analyzes narratives related to the food environment. Narrative data was collected from residents in Central Topeka, a neighborhood that relatively recently lost their neighborhood grocery store, a Dillon’s (a division of Kroger). This store was an important source for healthy food access in addition to providing access to other vital resources like a post office and pharmacy. Many low-income residents in the U.S. live in areas with little access and availability of healthy foods. These areas are known in the literature as food deserts. The gist of the food desert argument is that full service, large food retailers like supermarkets, that offer fresh produce and other healthy foods on a regular basis, are generally located physically further away from poor neighborhoods. This is ironic because poorer consumers tend to need healthy food and other important resources close at-hand because they are less likely than higher income consumers to possess reliable transportation, and often work evenings, weekends, and other irregular hours characteristic of low-wage employment. Food environments are commonly assessed by counting the sources of food (e.g., food stores, restaurants, convenience stores) and using GIS software to illustrate their distribution within a geographic unit. However, there has been comparatively less effort to assess perceptions of food environments. This study advances the qualitative, ground-level efforts to understand food insecurity and food deserts by incorporating cultural, interactional literature and methodological techniques. The project shows that narratives related to the food system, like narratives related to other aspects of social life, express our values, and are part of our “cultural repertoire” or “tool kit” for deciding what we think, and how we behave (Swidler 1986; McMillan Lequieu 2015). Major themes that emerge from the interview data include “narratives of loss,” social atomization, perceptions of disinvestment in Central Topeka, self-sufficiency, and lack of capital which decreases agency around planning meals, getting to and from food stores, and shopping for food. Besides health and nutrition, the local food environment and nearby stores are integral to identity and feelings of community and inclusiveness in a low-income neighborhood. Accessible food stores like Dillon’s are one last important source of agency and symbolic consumption for poor inner-city residents. The Dillon’s closing was a disappointing shock that perpetuated and perhaps amplified a feeling of non-inclusiveness and resentment toward the city government, residents in different areas of the city, and Dillon’s. There is a clear feeling among residents that exclusion and disinvestment in Central Topeka are simply “the way it is” and “the way it will always be.” The closing chapters assess the impacts of this loss on residents’ sense of agency, and the implications of this for future academic studies and applied research.
Keywords: Food insecurity; Food desert; Narrative; Agency; Qualitative